MOTIVACION DEL TALENTO HUMANO DEL ALMACEN TIA.S.A DE LA CUIDAD DE BABAHOYO - CONTRERAS JACOME, BLANCA MICHEL (2018)
Almacenes "TIA" S.A is a multinational company that is dedicated to the distribution and commercialization of home consumer products, and personnel in Ecuador has 187 branches nationwide, one of these branches is located in the City of Babahoyo in the streets Bolívar between García Moreno and June 5, which has been operating since 11 November 2001 Having the administrative matrix in the city of Guayaquil denotes the lack of control and compliance with respect to workers' rights, this has generated demotivation by the staff that is working in the branch of the city of Babahoyo (Almacenes TIA S.A.), being one of the weaknesses that keeps the company at no consider internal clients (employees) forgetting that they are the fundamental part of the company since they are conform the values, the quality and the service that they offer to the client external.